2022
DOI: 10.9734/ijecc/2022/v12i121468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorous and Potassium on Growth Parameters, Yield and Yield Attributes of Chickpea (Cicer arietinum L.) under the Rainfed Condition in Chitrakoot, India

Abstract: The present study investigate the effect of phosphorous and potassium on growth parameters, yield and yield attributes of chickpea (Cicer arietinum L.) under the rainfed condition in Chitrakoot, India. Field experiments were carried out to investigate the effect of phosphorus and potassium on chickpea growth parameters, yield components, and yield during the rabi season of 2021-22 at Rajoula Agriculture farm, Mahatma Gandhi Chitrakoot Gramodaya Vishwavidyalaya Chitrakoot, Satna (M.P.). The experiment consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…These results are consistent with what was found by [32,33,34] The results of Table (6) showed that there was a significant difference among the levels of the Optimus-plus (bio-fertilizer) in terms of the number of spikes, as it reached (428.06 spikes.m -2 ) at the level of (150 ml.100 L of water -1 ), the reason for the increase in the number of spikes is that the amino acids present in the bio-fertilizer and the organic materials contributed to an increase in cell expansion, which ultimately led to an increase in the spikes number. This result is in line with what was reported by [35,36].…”
Section: Spikes No (Spikes M -2 )supporting
confidence: 94%
“…These results are consistent with what was found by [32,33,34] The results of Table (6) showed that there was a significant difference among the levels of the Optimus-plus (bio-fertilizer) in terms of the number of spikes, as it reached (428.06 spikes.m -2 ) at the level of (150 ml.100 L of water -1 ), the reason for the increase in the number of spikes is that the amino acids present in the bio-fertilizer and the organic materials contributed to an increase in cell expansion, which ultimately led to an increase in the spikes number. This result is in line with what was reported by [35,36].…”
Section: Spikes No (Spikes M -2 )supporting
confidence: 94%
“…Nitrogen, phosphorus and potassium are deficit in soil under chickpea cultivation in Punjab (Pakistan). The N, P and K are indispensable to improve growth, yield and yield attributes of chickpea (Rajput, 2018;Tembhare et al, 2022). Nitrogen is a crucial nutrient for plant growth and development, plays a key role in photosynthesis, phytohormonal regulation, proteomic changes, and overall, to complete plant lifecycle.…”
Section: Resultsmentioning
confidence: 99%
“…Potassium also plays a key role in nitrogen metabolism (Xu et a., 2020) and thus improves nitrogen use efficiency. co-application of phosphorus with nitrogen (Ivanov et al, 2021) and phosphorus with potassium is proved to offer higher yield than their individual use in chickpea (Ali et al, 2010;Tembhare et al, 2022). Expensive potassium fertilizers are the primary reason for avoiding potassium application in pulses.…”
Section: Introductionmentioning
confidence: 99%